Latour and the passage of law - McGee, Kyle (Critical connections, 2015)
This exciting new vision for legal theory combines analytical tools drawn from Latour's actor-network theory with the philosophical anthropology of the Moderns in An Inquiry into Modes of Existence to blaze a new trail in legal epistemology